APOBEC3G/3A Expression in Human Immunodeficiency Virus Type 1-Infected Individuals Following Initiation of Antiretroviral Therapy Containing Cenicriviroc or Efavirenz - Covino, Daniela A.; Purificato, Cristina; Catapano, Laura; Galluzzo, Clementina M.; Gauzzi, Maria Cristina; Vella, Stefano; Lefebvre, Eric; Seyedkazemi, Star; Andreotti, Mauro; Fantuzzi, Laura (Frontiers in Immunology, 2018)
Apolipoprotein B mRNA editing enzyme catalytic polypeptide-like 3 (APOBEC3) family members are cytidine deaminases that play crucial roles in innate responses to retrovirus infection. The mechanisms by which some of these enzymes restrict HIV-1 replication have been extensively investigated in vitro. However, little is known regarding how APOBEC3 proteins affect the pathogenesis of HIV-1 infection in vivo and how antiretroviral therapy influences their expression. In this work, a longitudinal analysis was performed to evaluate APOBEC3G/3A expression in peripheral blood mononuclear cells of antiretroviral-naive HIV-1-infected individuals treated with cenicriviroc or efavirenz at baseline and 4, 12, 24 and 48 weeks post-treatment follow-up. While APOBEC3G expression was unaffected by therapy, APOBEC3A levels increased in cenicriviroc but not efavirenz arm at week 48 of treatment. APOBEC3G expression correlated directly with CD4+ cell count and CD4+/CD8+ cell ratio, whereas APOBEC3A levels inversely correlated with plasma soluble CD14. These findings suggest that higher APOBEC3G/3A levels may be associated with protective effects against HIV-1 disease progression and chronic inflammation and warrant further studies.